State Border Management Cooperation and the Fulfillment of Economic Rights of Border Communities of West Kalimantan-Sarawak - Bangun, Budi Hermawan (Indonesian Journal of International Law, 2018)
One of state’s border management cooperation between West Kalimantan and Sarawak is done through socio-economic cooperation, which has the goals to improve the border community’s prosperity. Although people in the border have a socio-cultural similarities, there are differences in the level of welfare because infirmity of state presence in fulfilling their economic rights. This condition causes the border communities have tendency to depend on neighboring countries and maintain transnational economic relations, even though they have to breaking the national law. These facts show that in essence, the bilateral cooperation agreement between Indonesia and Malaysia has not provided optimal fulfillment of the economic rights of border communities of West Kalimantan with Sarawak.